Thinking Through the Box: Evaluating a 3D Game to Engage Penetrative Thinking - Pathak, Aarohi; Chang, Jack S. K.; Resch, Gabby; Doucette, Alison; Yeboah, Georgina; Welsh, Timothy Nevin; Nitsche, Michael; Mazalek, Ali (Frontiers in Virtual Reality, 2020)
Spatial skills allow us to mentally imagine and manipulate objects and their spatial relations. These skills are crucial in both everyday and expert tasks. The present paper reports on an evaluation of a tangible virtual reality system developed to train a specific spatial skill known as penetrative thinking - the ability to imagine cross-sections of 3D objects from their surface features. In the system, users operate a tangible interface to make cuts through 3D objects in a series of spatial puzzles. Users operate the tangible interface to position a virtual plane until a “slice” at its location matches a target cross-section of a virtual object. Multiple spatial puzzles combine to form a game-like environment in VR. The system was evaluated in two stages (n=45; n=6). Although there were ultimately no significant pre-/post-intervention changes in measured penetrative thinking, participants’ performance on the novel VR task correlated with scores on a standardized test of penetrative thinking (Santa Barbara Solids Test). These findings provide evidence that the new system and the standardized test accessed similar spatial skills As a consequence, coupling VR with a tangible and embodied interface has the potential to be a valid approach for training penetrative thinking skills.